Perkembangan Moral Pada Anak - Maharani, Laila (Universitas Islam Negeri Raden Intan Lampung, 2014)
This study aims to review the moral development of children. In attitudes and moral behaviors implied values are held with regard to the value of something that is said to be good and right, proper, and should happen. The problem is why the attitude of moral development in children today is increasingly apprehensive. Mostly passed from generation to generation through a lifelong educational process. There are values that need to be maintained, some are assimilated toward progress or progressive change, but some are altered or shifted due to various factors that influence it. This model is expected to be one of our mechanisms as parents, teachers, and society needs to understand the development of moral attitudes in order to help learners develop a moral attitude that is desirable, educate learners to be good children, and be morally good and right.